Empowering Female Legislators in the South Sulawesi Regional People's Representative Council (International Journal of Applied Research and Innovation, 2026)
This study examines the strengthening of female legislators in the Regional People's Representative Council of South Sulawesi through a mixed empirical–normative socio-legal approach. It integrates doctrinal analysis of statutory frameworks with qualitative field data derived from interviews, document analysis, and legislative records to construct a context-sensitive empowerment model. The findings reveal that despite formal guarantees of gender equality within Indonesian legal frameworks, female legislators continue to face structural, cultural, and institutional constraints that limit their substantive participation in legislative functions. Empirical evidence highlights gaps in institutional support, unequal access to strategic political positions, and the persistence of patriarchal norms influencing legislative dynamics. The study develops a multidimensional empowerment model consisting of legal reinforcement, institutional restructuring, and capacity enhancement, which is validated through triangulation and expert evaluation. This model demonstrates the importance of aligning legal mandates with institutional practices and individual competencies to achieve gender-responsive governance. The research contributes to socio-legal scholarship by offering an empirically grounded and normatively informed framework for strengthening women’s legislative roles in decentralized political systems.